PENGEMBANGAN PROTOTYPE SISTEM INFORMASI MANAJEMEN UNTUK JASA INSTALASI DAN TROUBLESHOOTING JARINGAN INTERNET - Donesa Rucci; Anie Rose Irawati; Didik Kurniawan (Jurnal Komputasi, 2016)
Nowadays the internet is growing rapidly including in Indonesia. Internet has become an essential requirement for everyone to get information or other purposes. The benefits of internet make Â many people use the internet as appliances for supporting their activities. The use of internet has an impact on the increasing demand to the internet services provider. Internet provider is a company which engaged in providing internet services. In the process of instalation and troubleshooting for internet network, the provider requires a management information system which is used to organize the division of task for handling the installation and troubleshooting of internet network. The internet provider who has not had a management system yet, will get difficulties to devide the tasks of their employees for handling the process of installation and troubleshooting of the internet network. This research, created a management information system for installation and troubleshooting of internet network service which is recieve the information of internet interference from the customers and help in handling process division of tasks for installing and troubleshooting of internet network. This management information system was created using PHP (Hypertext Prepocessor) and some plugins such as twitter bootstrap and high chart. The result of Black Box testing showed that this management information system for installation and troubleshooting of internet network service has been successfully created as the users need.Keywords: Internet, Internet Service Provider (ISP), Management Information Systems (MIS), PHP.